RP-HPLC Determination of Voriconazole in Pure and Pharmaceutical Dosage Forms - Gowri Sankar, D.; Nagesh Babu, A.; Rajeswari, A.; Vamsi Krishna, M. (Asian Journal of Chemistry, 2010)
A reverse phase high performance liquid chromatographic (RP-HPLC) method has been developed for the estimation of voriconazole in bulk and pharmaceutical formulations. The quantification was carried out using a RP-C-18 Hypersil BDS column (250 mm × 4.6 mm i.d., 5 μ particle size) in isocratic mode with mobile phase comprising water, acetonitrile and methanol in the ratio of 50:25:25 v/v. The mobile phase was pumped at a rate of 1.5 mL/min and detection was carried out at 256 nm. The linearity was found to be in the range of 20-400 μg/mL. The proposed method was statistically evaluated and can be applied for routine quality control analysis of voriconazole in tablets.